IMPACT OF PLANTING METHODS ON WHEAT GRAIN YIELD AND YIELD CONTRIBUTING PARAMETERS - G. Abbas; M. A. Ali; G. Abbas; M. Azam; I. Hussain (Journal of Animal and Plant Sciences, 2009)
A field experiment was carried out during two consecutive years 2006-07 and 2007-08 at two locations in arid area of the Punjab province. The objective of the study was to compare conventional planting method (broadcasting) of wheat sowing with drill planting method for grain yield and its parameters. The experiment comprised of four (15,22.5 and 30 cm spaced rows ad broad casting) treatments arranged in randomized complete block design with three replications in a net plot size of 12x17 m. The results over the years of the study revealed that the germination were statistically at par in drill sowing at 15 cm apart rows and broadcasting. Better plant height was noted in drill planting with 30 and 22.5 cm rows. However, number of spikelets spike –1 and number of grains spike-1 were statistically similar in broadcasting and drilling at 22.5 cm apart rows. Similar 1000-grain weight was recorded in drill sowing at 30, 22.5 cm and broadcasting. The maximum grain yield was obtained through broadcast method and it was statistically at par with drill planting method where row spacing was 22.5 cm. Whereas, drill-planting techniques with row spacing 15 cm and 30 cm, were inferior to broadcast method. It may be concluded that broadcast method is suitable for wheat sowing in sandy loam soils of arid area.
Keywords: Triticum aestivum L; planting methods; NPK fertilizers; Arid; Pakistan